2012
DOI: 10.4103/2230-8210.98004
|View full text |Cite
|
Sign up to set email alerts
|

Drugs affecting HbA1c levels

Abstract: Glycated hemoglobin (HbA1c) is an important indicator of glycemic control in diabetes mellitus, based on which important diagnostic and therapeutic decisions are routinely made. However, there are several situations in which the level of HbA1c may not faithfully reflect the glycemic control in a given patient. Important among these is the use of certain non-diabetic medications, which can affect the HbA1c levels in different ways. This review focuses on the non-diabetic medications which can inappropriately ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 24 publications
1
23
0
6
Order By: Relevance
“…It is possible, however, that some of the study participants who only provided Bio-Rad HbA 1c samples possessed some form of hemoglobinopathy. Additionally, there may be other factors such as prescription medication which may contribute to altered HbA 1c values [26] and it should be noted that this data was not captured by the risk questionnaire during this study. Adding questions regarding medication use would increase the complexity and duration of completing the questionnaire which would increase subject burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that some of the study participants who only provided Bio-Rad HbA 1c samples possessed some form of hemoglobinopathy. Additionally, there may be other factors such as prescription medication which may contribute to altered HbA 1c values [26] and it should be noted that this data was not captured by the risk questionnaire during this study. Adding questions regarding medication use would increase the complexity and duration of completing the questionnaire which would increase subject burden.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of HbA 1c was incorporated into clinical practice in the 1980s after studies demonstrated that it correlates with blood glucose measurements (3,4). Today, it is used as an indicator of glycemic control and as a diagnostic test for diabetes mellitus (4).…”
Section: Discussionmentioning
confidence: 99%
“…Today, it is used as an indicator of glycemic control and as a diagnostic test for diabetes mellitus (4). HbA 1c is formed by nonenzymatic condensation of glucose with the N-terminal valine residue of the β chains of hemoglobin (4,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A HbS, por sua vez, é responsável por acarretar em valores falsamente aumentados desse parâmetro 39 . Níveis elevados de hemoglobina fetal, HbF, utilizada através do medicamento hidroxiureia para tratamento da anemia falciforme, por exemplo, pode resultar na diminuição dos níveis da HbA1c 40 . Ingestão crônica de aspirina e/ou altas doses de vitamina E e C, assim como outros antioxidantes, podem diminuir a concentração de HbA1c pois causam a inibição de glicação da hemoglobina 41 .…”
Section: Kidney Intunclassified